Effect of Higher Landau Levels on the Transverse Thermoelectric Conductivity in High-\(T_c\) Superconductors - Tinh, Bui Duc (Communications in Physics, 2017)
We investigate effect of higher Ladau levels on the transverse thermoelectricconductivity \(α_xy\), describing the Nernst effect in high-\(T_c\) superconductors, by using the time-dependent Ginzburg-Landau theory in two dimensional model withthermal noise. The transverse thermoelectric conductivity is calculated inthe self-consistent Gaussian approximation. Our results indicate that thehigher Landau levels are, the less these levels contribute to the transversethermoelectric conductivity. Our results are in good agreement with experimental dataon high-Tc superconductor